The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.ijom.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the association between platelet-rich fibrin and bovine bone on bone regeneration. A histomorphometric study in the calvaria of rats

Abstract: This study aimed to investigate the effects of platelet-rich fibrin (PRF) associated or not with Bio-Oss on bone defects in the calvaria of rats. A critical-size defect of 5-mm diameter was performed in the calvaria of 48 rats. These animals were divided into six groups of eight animals each, according to the treatment received: homogeneous clot, autogenous clot, autogenous PRF, homogeneous PRF, Bio-Oss, or Bio-Oss associated with PRF. The animals were euthanized after 30 or 60 days. Bone regeneration was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 24 publications
1
45
0
4
Order By: Relevance
“…Griffin et al showed in a systematic review that although early clinical results suggest that the use of PRP is safe and feasible, however presents with no clinical benefit in either acute or delayed fracture healing was observed and therefore its use in bone regeneration was not undetermined [61]. While other models have also shown favorable results on new bone formation with platelet concentrates [6365], the results from our study showed that PRP had little influence on osteoblast differentiation (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…Griffin et al showed in a systematic review that although early clinical results suggest that the use of PRP is safe and feasible, however presents with no clinical benefit in either acute or delayed fracture healing was observed and therefore its use in bone regeneration was not undetermined [61]. While other models have also shown favorable results on new bone formation with platelet concentrates [6365], the results from our study showed that PRP had little influence on osteoblast differentiation (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…However, in another set of experiments, it was found that PRP had significant beneficial effects on improving the rate of wound healing and fat graft survival rates and in enhancing bone graft regeneration [6,7]. The application of PRP with Biop-Oss onto bone defects resulted in an increase in granulation, but only when associated with Bio-Oss [3]. Finally, the influences of PRP on cells in vitro were examined to see whether its influences are indicative of those required for wound healing in vivo [3].…”
Section: General Introductionmentioning
confidence: 99%
“…The application of PRP with Biop-Oss onto bone defects resulted in an increase in granulation, but only when associated with Bio-Oss [3]. Finally, the influences of PRP on cells in vitro were examined to see whether its influences are indicative of those required for wound healing in vivo [3].…”
Section: General Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, when adding PRF to an alloplastic graft (HA/β‐ TCP) or autologous graft, a significantly increased regeneration of calvarial defects was observed both at 4 and 8 weeks compared to the use of PRF or the grafts alone (Acar, Yolcu, Gul, Keles & Erdem, ; Pripatnanont, Nuntanaranont, Vongvatcharanon & Phurisat, ). Conflicting results were reported when combining PRF to DBBM (Oliveira, deC Silva, Ferreira, Avelino & Garcia, ; Pripatnanont et al., ; Yoon, Lee & Yoon, ). Similar regeneration outcomes were observed when rat calvarial CSDs were treated with PRF or demineralized bone matrix (Sindel, Dereci, Toru & Tozoglu, ).…”
Section: Resultsmentioning
confidence: 98%